POLEMIK TEORI KENABIAN PERSPEKTIF FILOSOF MUSLIM (STUDI KOMPARASI PEMIKIRAN AL-FARABI DAN ABUBAKAR AL-RAZI) - Ubaidillah Anshari (Universitas Pahlawan Tuanku Tambusai, 2023)
The most important basis for the knowledge of muslim philosophers is reason and revelation, while revelation is unacceptable to logical reason, and revelation is the source of knowledge that only god gives to prophets.This is where the prophetic polemic between the thoughts of Muslim philosophers.The Muslim philosopher is Al-Farabi who generally accepts prophetic theory, and there is a Muslim philosopher who rejects the prophetic theory is Abu Bakr Al-Razi.This becomes a phenomenon that occurs in the thinking of Muslim philosophers. According to Al-Farabi it is that the prophet was very closely related to the philosopher because both were able to communicate with the tenth sense (Gabriel).And a prophet must get revelation, so that when he communicates with the mind of the fa'al he is able to grasp all the truth that comes from the mind of the fa'al.While according to Al-Razi that there is no need for prophets, because Allah created reason for man, with human reason can know more everything including knowing the whole and his Lord.In the works entitled Bar al-Sa'ah and Sirr al-israr, Al-Razi wrote this kind of phrase,